Geophysical subsurface profiling of Kuantan bauxite formation - Muhammad Hanif, Muhamad (2019)
This research focuses on the geophysical subsurface profiling of Kuantan bauxite formation. At the past time, the conventional, borehole sampling incorporated with Mackintosh Probe (MP) is used for a purposed to investigate the subsurface of the soil. However, the MP is very costly and lengthily. The objective of this research is to study the geophysical method to determine the subsurface profile by using resistivity image and to correlate the data of electrical resistivity and MP. The result of image profile was illustrated that the resistance of soil is depended on type of soil strata and soil formation. As a result, the image profile generated by the software demonstrated in virtual the geophysical subsurface soil imaging. The data from results of MP test was tabulated to represent the hardness of the soil and the data of electrical resistivity was interpreted to correlate with the both result. The correlation intersection is depended on the depth from ground surface against the number of mackintosh blows and soil resistivity. The more the value of resistivity, the more the Mackintosh blows. It can conclude that the resistivity increase proportional with mackintosh blows.